Tema ljubezni skozi prizmo simbolnega v pripovedni prozi Andreja Hienga - Zver, Gabriela (Jezik in slovstvo, 2005)
True love cannot be foud in the prose of Hieng - there is only a wish for love and a lot of hate, rooted in the feelings of guilt, in pathological forms of love, in past humiliation and shame. Therefore adequate symbols are chosen by Hieng: he portrays the world of narcissists who see their lives as a carefully tended park and, in addition, adore the world of cards, as they love to play with the destinies of other people, although at the same time, they do not wish to be emotionally over-involved in them, since they live in the world of lace, where order,peace and comfort rule their burgeois world, and in the world of magicians, where manipulation of others is made possible to them. Carefully selected colours and adequare musical instruments are strong players contributing to the image of Hieng's bourgeois world.
Keywords: Hieng, Andrej, 1925-2000; Literarni junaki; slovenska proza; 20.st.; ljubezen; love; literarni motivi; literarne teme; literarna interpretacija; simboli; symbol; barve; glasbila